1999
DOI: 10.4269/ajtmh.1999.61.825
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A in Latin America: a changing epidemiologic pattern.

Abstract: Abstract. In a multicenter study, hepatitis A virus (HAV) seroprevalence was surveyed in six countries in Latin America in which in 12,000 subjects were stratified for age. The highest rates of seroprevalence were recorded in the Dominican Republic (89.0%) and Mexico (81.0%), with lower rates in Brazil (64.7%), Chile (58.1%), Venezuela (55.7%), and Argentina (55.0%). The seroprevalence of HAV in children between 1 and 5 years of age was less than 50%, except in the Dominican Republic. In the 5-10-year-old age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
0
8

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 10 publications
6
94
0
8
Order By: Relevance
“…These studies have found patterns of prevalence of antibodies to hepatitis A virus, which depend on the local environmental conditions and standard of living of the study population [4,5]. These patterns fit broadly into three groups -of high, medium and low endemicity -which each have different implications for intervention strategies [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have found patterns of prevalence of antibodies to hepatitis A virus, which depend on the local environmental conditions and standard of living of the study population [4,5]. These patterns fit broadly into three groups -of high, medium and low endemicity -which each have different implications for intervention strategies [6].…”
Section: Introductionmentioning
confidence: 99%
“…Low endemicity is found in the relatively well-off areas of large cities where water supply and domestic hygiene have reached adequate levels, while high endemicity persists in the lowincome urban periphery and rural areas. Studies from Latin America have usually found this mixed pattern [6]. In the first, low prevalence group, the main intervention strategy is immunization of specific groups or of the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Because no nationwide seroprevalence study has been conducted with a sample size adequate for stratification by region and age, hepatitis A seroprevalence was estimated based on reports from areas with below-average (26)(27)(28), average (10,29,30) and aboveaverage (31, 32) infection rates, compared with Argentina as a whole. The Northeast and Central regions were considered to have below-average endemicity, the South region had average endemicity, and the Cuyo and Northwest regions had above-average endemicity.…”
Section: Force Of Hepatitis a Infectionmentioning
confidence: 99%
“…A United States model of intrahousehold transmission (33) was adapted to Argentina to account for larger household sizes (34), higher rates of hepatitis A immunity (10,(26)(27)(28)(29)(30)(31)(32), and more recent data on agespecific probabilities that hepatitis A infections will cause overt disease (4). The model predicts the number of secondary cases resulting from personal contact with individuals infected with hepatitis A based on household size, age distribution, and age-specific probabilities of having hepatitis A immunity.…”
Section: Hepatitis a Transmission Through Personal Contactmentioning
confidence: 99%
See 1 more Smart Citation